Early Environmental and Biological Influences on Preschool Motor Skills: Implications for Early Childhood Care and Education - Escolano-Pérez, Elena; Sánchez-López, Carmen Rosa; Herrero-Nivela, Maria Luisa (Frontiers in Psychology, 2021)
Early motor skills underpin the more complex and specialized movements required for physical activity. Therefore, the design of interventions that enhance higher levels of early motor skills may encourage subsequent participation in physical activity. To do so, it is necessary to determine the influence of certain factors (some of which appear very early) on early motor skills. The objective of this study was to examine the influence of some very early environmental variables (delivery mode, feeding type during the first 4 months of life) and some biological variables (sex and age in months) on preschool motor skills, considered both globally and specifically. The sample was composed by 43 preschool students aged 5-6 years. The participant’s parents completed an ad hoc questionnaire, reporting on delivery mode, feeding type, sex, and age in months. The children’s motor skills were assessed using observational methodology in the school setting, while the children participated in their regular motor skills sessions. A Nomothetic/Punctual/Multidimensional observational design was used. Results revealed that certain preschool motor skills were specifically influenced by delivery mode, feeding type, sex, and age. Children born by vaginal delivery showed higher scores than children born via C-section in throwing (p = 0.000); total control of objects (p = 0.004); total gross motor skills (p = 0.005); and total motor skills (p = 0.002). Children who were exclusively breastfed outperformed those who were formula-fed in throwing (p = 0.016); visual-motor integration (p = 0.005); total control of objects (p = 0.002); total gross motor skills (p = 0.023); and total motor skills (p = 0.042). Boys outperformed girls in throwing (p = 0.041) and total control of objects (p = 0.024); while the opposite occurred in static balance (p = 0.000); visual-motor coordination (p = 0.020); and total fine motor skills (p = 0.032). Older children (aged 69-74 months) obtained higher scores than younger ones (aged 63-68 months) in dynamic balance (p = 0.030); visual-motor integration (p = 0.034); and total balance (p = 0.013). Implications for early childhood care and education are discussed since this is a critical period for motor skill development and learning.